2016
DOI: 10.1177/2066220316637390
|View full text |Cite
|
Sign up to set email alerts
|

It takes two to tango: Offenders’ involvement in decisions regarding sanctions, measures and conditions in light of the ERCSM and the ERProb. A Dutch case study

Abstract: This article examines the question to what extent offenders are involved in decisions regarding the sanction, measure and/or conditions that have been imposed upon them. More specifically, the article focuses on the offender's involvement in the stage of implementation (or enforcement) of a conditional sentence or measure. It analyses Dutch legislation and practice on this point and evaluates them in light of the relevant provisions of the European Rules on Community Sanctions and Measures and the European Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…More recently, the focus on the experience of the offender has been augmented by studies in the area of desistance, which suggest that effective interventions are those that: engage with offenders in a positive and respectful way (Maruna and Farrall, 2004;Rex, 1999); encourage them to co-participate in the supervision process (Rex, 1999;McCulloch, 2013); facilitate the subjective transformations of self (Maruna, 2001); use wisely the potential of a 'good relationship' (Burnett and McNeill, 2005;Morash et al, 2015;Skeem et al, 2007); and provide practical help when needed (Farrall, 2002). Weaver and Barry (2014) state that the process of change which is fundamental for the intended outcomes of supervision (community safety, social rehabilitation and reintegration) cannot be achieved without the offender's participation and active involvement in the process, and Ansems and Braam (2016) found that probation officers realize the importance of involving probationers and act upon this belief.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the focus on the experience of the offender has been augmented by studies in the area of desistance, which suggest that effective interventions are those that: engage with offenders in a positive and respectful way (Maruna and Farrall, 2004;Rex, 1999); encourage them to co-participate in the supervision process (Rex, 1999;McCulloch, 2013); facilitate the subjective transformations of self (Maruna, 2001); use wisely the potential of a 'good relationship' (Burnett and McNeill, 2005;Morash et al, 2015;Skeem et al, 2007); and provide practical help when needed (Farrall, 2002). Weaver and Barry (2014) state that the process of change which is fundamental for the intended outcomes of supervision (community safety, social rehabilitation and reintegration) cannot be achieved without the offender's participation and active involvement in the process, and Ansems and Braam (2016) found that probation officers realize the importance of involving probationers and act upon this belief.…”
Section: Introductionmentioning
confidence: 99%